BIOFILTOTACUM : OPTIMALISASI LIMBAH NICOTIANA TABACUM SEBAGAI MEMBRAN ULTRAFILTRASI DALAM FILTER AIR SUNGAI - Siti Hadiyati Arifah; Kharisma Dian Nurani; Mahdalina Mursilati; Gembong Haryono (Universitas Tidar, 2018)
Research on Biofiltotacum - The optimization of stem waste (Nicotianatabacum) aims to create a bio-filter from cellulose extracts of tobacco stems as a form of ultrafiltration membrane for river water filters. Tobacco stem waste can be utilized as an efficient and effective membrane feedstock. This research is done by phase inversion method. Quantitative data analysis was obtained with the calculation of acetyl content that is 16, 89%. Acetylation data obtained is smaller than the standard of 40%. The amount of acetyl content can be affected by several factors, including duration of acetylation process, temperature, stirring speed, acetate amount, and also solvent amount. In addition, the small amount of acetyl may be caused by the cellulose content in the tobacco rod is not yet optimally isolated.